Position correction in ptychography using hybrid input–output (HIO) and cross-correlation. (14th February 2019) - Dwivedi, P; Konijnenberg, A P; Pereira, S F; Meisner, J; Urbach, H P
Abstract: Ptychography is a form of coherent diffractive imaging; it employs far-field intensity patterns of the object to reconstruct the object. In ptychography, an important limiting factor for the reconstructed image quality is the uncertainty in the probe positions. Here, we propose a new approach which uses the hybrid input–output algorithm and cross-correlation in a way that can correct our estimates of the probe positions. The performance and limitations of the method in the presence of noise, varying overlap, and maximum recoverable error are studied using simulations. A brief comparison with other existing methods is also discussed here.